Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12974-020-1714-y
|View full text |Cite
|
Sign up to set email alerts
|

High-salt diet does not boost neuroinflammation and neurodegeneration in a model of α-synucleinopathy

Abstract: Aim: Pre-clinical studies in models of multiple sclerosis and other inflammatory disorders suggest that high-salt diet may induce activation of the immune system and potentiate inflammation. However, high-salt diet constitutes a common non-pharmacological intervention to treat autonomic problems in synucleinopathies such as Parkinson's disease and multiple system atrophy. Since neuroinflammation plays an important pathogenic role in these neurodegenerative disorders, we asked here whether high-salt diet may ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…While we cannot exclude the possibility that our experimental strategies were insufficient to characterize the complete responses of microglia to HSD, no study has yet reported that either sterile inflammatory ligands or diet‐induced systemic inflammation induces immunological memory in tissue‐resident macrophages (Dominguez‐Andres et al , 2022). Given that the effects of HSD on microglia and macrophage polarization remain debatable (Amara et al , 2016; Heras‐Garvin et al , 2020; Zhang et al , 2020), future work evaluating microglial responses through high‐throughput sequencing could be informative. Investigation of whether innate immune memory can be triggered in different tissue‐resident macrophage populations after HSD and the contribution of these populations to disease progression represents a fascinating area of research.…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot exclude the possibility that our experimental strategies were insufficient to characterize the complete responses of microglia to HSD, no study has yet reported that either sterile inflammatory ligands or diet‐induced systemic inflammation induces immunological memory in tissue‐resident macrophages (Dominguez‐Andres et al , 2022). Given that the effects of HSD on microglia and macrophage polarization remain debatable (Amara et al , 2016; Heras‐Garvin et al , 2020; Zhang et al , 2020), future work evaluating microglial responses through high‐throughput sequencing could be informative. Investigation of whether innate immune memory can be triggered in different tissue‐resident macrophage populations after HSD and the contribution of these populations to disease progression represents a fascinating area of research.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral hippocampal CA3 and DG fields of three 15 μm-thick consecutive coronal sections corresponding to bregma 1.82 mm to bregma 2.46 mm were captured at 20× magnification and digitized. The percentage of positively stained areas of Iba1, IL-1β, IL-6 or caspase 8 was quantified using ImageJ [ 19 ]. Three independent experiments were performed, and data was averaged per slide before statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The deviation was found to be accompanied by an increase of CD3 + , CD4 + and CD8 + in the same regions. Interestingly, an increased salt diet activated inflammation in various diseases, but does not induce neuroinflammation and neurodegeneration in α-synucleinopathies [ 231 ]. It is also stressed that the elevated iNOS expression in MSA is correlated with neuroinflammation and neuronal loss [ 232 ].…”
Section: Various Neurodegenerative Factorsmentioning
confidence: 99%